2016
DOI: 10.1016/j.ydbio.2016.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Essential function of the transcription factor Rax in the early patterning of the mammalian hypothalamus

Abstract: The hypothalamus is a region of the anterior forebrain that controls basic aspects of vertebrate physiology, but the genes involved in its development are still poorly understood. Here, we investigate the function of the homeobox gene Rax/Rx in early hypothalamic development using a conditional targeted inactivation strategy in the mouse. We found that lack of Rax expression prior to embryonic day 8.5 (E8.5) caused a general underdevelopment of the hypothalamic neuroepithelium, while inactivation at later time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 54 publications
(111 reference statements)
3
58
0
Order By: Relevance
“…Thus, the more severely affected SCN phenotype seen in the current study seem to reflect differences in development of the eye between the Rax CKO and the ZRDCT mouse strain. The diverse hypothalamic phenotypes of the ZRDCT mouse strain may also reflect reduced levels of RAX protein in the developing hypothalamus, where expression of Rax in the hypothalamic neuroepithelium, as in other parts of the forebrain, is required for proper neurogenesis (VanDunk et al 2011;Orquera et al 2016). However, in the current study the observed SCN phenotype is not a direct consequence of deleted Rax expression in the hypothalamus, since the Crx-driven Cre recombinase is expressed only in the retina and pineal gland (Nishida et al 2003;Omori et al 2011).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Thus, the more severely affected SCN phenotype seen in the current study seem to reflect differences in development of the eye between the Rax CKO and the ZRDCT mouse strain. The diverse hypothalamic phenotypes of the ZRDCT mouse strain may also reflect reduced levels of RAX protein in the developing hypothalamus, where expression of Rax in the hypothalamic neuroepithelium, as in other parts of the forebrain, is required for proper neurogenesis (VanDunk et al 2011;Orquera et al 2016). However, in the current study the observed SCN phenotype is not a direct consequence of deleted Rax expression in the hypothalamus, since the Crx-driven Cre recombinase is expressed only in the retina and pineal gland (Nishida et al 2003;Omori et al 2011).…”
Section: Discussionmentioning
confidence: 62%
“…; Orquera et al . ). However, in the current study the observed SCN phenotype is not a direct consequence of deleted Rax expression in the hypothalamus, since the Crx ‐driven Cre recombinase is expressed only in the retina and pineal gland (Nishida et al .…”
Section: Discussionmentioning
confidence: 97%
“…Upon hypothalamic induction, genes encoding secreted morphogens are expressed within restricted regions of the hypothalamus, such as Bmp4, Fgf8, Fgf10 and Wnt8b in the caudal hypothalamus and Shh in the rostral hypothalamus (Lako et al, 1998;Orquera et al, 2016;Zhao et al, 2012), all of which may play a role in hypothalamic patterning. Indeed, a hypothalamic patterning defect was reported in mice lacking noggin, which encodes a Bmp antagonist (Davis and Camper, 2007).…”
Section: Early Patterning Of the Hypothalamusmentioning
confidence: 99%
“…Shh expression may also be mediated by Rx3/Rax, as in both zebrafish rx3 and mouse Rax mutants, Shh expression is lost accompanied by a hypothalamic patterning defect (Muthu et al, 2016;Orquera et al, 2016). Interestingly, this phenotype is only observed when Rax is knocked out prior to embryonic day (E) 8.5 in mouse embryos, whereas a more specific defect in specification and differentiation of hypothalamic neurons is revealed when Rax is knocked out later (Lu et al, 2013;Orquera et al, 2016).…”
Section: Box 2 Modular Changes In Hypothalamic Anatomy: a Means To Ementioning
confidence: 99%
“…Do gene knockout studies provide insight into how the mouse hypothalamus is built? Previous gene knockout studies have suggested two major transcriptional programmes of hypothalamic development: a Fezf2/Olig2/Otp/Sim1 programme, which generates neurones of the PVN, PeVN, SON and SCN that occupy the anterior hypothalamus, and a Nkx2.1‐Shh‐Rx progenitor programme, which generates neurones of the tuberal hypothalamus, including those of the VMN and ARC; Placzek M., Fu T., Towers M. (submitted) . Thus, for example, initial reports suggested that the PVN/PeVN/SON/SCN, but not the ARC, can be detected in mice that lack functional Nkx2.1, whereas Lhx1 (a marker of the SCN) is still detected after genetic‐inactivation of Shh .…”
Section: Anisotropic Growth Model and Hypothalamic Organisationmentioning
confidence: 99%